THE INFLUENCE FAKTORS ON PROJECT PERFORMANCE: INTEREST, COMPETENCY AND CONTRACT PROJECT - Ladika, Ladika; Sanggoro, Heru Bayuaji (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
In order to increase economic growth through the development of industrial areas in Indonesia, the Government is making efforts to accelerate projects that are considered strategic and have high urgency so that they can be realized within a short period of time. A project is considered successful if good project performance is achieved. Competence of project funds is important. This research was conducted to determine the influence of competence, interests and project contracts which are thought to have an impact on project performance. This research contained 55 samples and used the smarPLS method. From the results of this research, it was found that there was a significant influence on project interests and competencies. This shows that the competencies possessed by the project team are very influential. Apart from competency, the results obtained from project interests have an influence on project performance. But this is not the case with project contracts which do not include any influence on project performance.